Prediction of Trolling behavior from sadism and Internet addiction in young adults of Buenos Aires - Pablo Christian González Caino; Santiago Resett (Interacciones)
Background: Trolling is a very topical phenomenon, but much less studied unlike other problems related to new technologies. The present study evaluated the levels of trolling in adults from sadism and internet addiction. Method: For this purpose, an intentional sample of 708 adults of both genders (56% women, age M = 25 years SD = 8.7), from the Autonomous City of Buenos Aires (CABA) and Greater Buenos Aires (GBA), Argentina is selected. Participants answered the Trolling Questionnaire by Buckels et al., On Sadistic Tendencies by Paulhus et al., On Internet Addiction by Lam-Figueroa et al. and a demographic questionnaire. The data indicated that both vicarious sadism, outright sadism, and dysfunctionality in Internet use were predictors of trolling. Results: The results suggested an association of trolling with age and differences according to gender. A structural model to predict trolling based on sadism as a latent variable and internet addiction shows an adequate fit CFI = .99, TLI = .98, RMSEA = .04, indicating that sadism predicted trolling and internet addiction. Conclusion: Sadism is an important predictor for trolling behavior over the internet, where individuals with these characteristics take advantage of anonymity to carry out their aggressive behaviors.